2021
DOI: 10.1111/febs.16060
|View full text |Cite
|
Sign up to set email alerts
|

Approaching transglutaminase from Streptomyces bacteria over three decades

Abstract: Transglutaminases are protein cross-linking and protein modifying enzymes that have attracted considerable interest due to their causal involvement in various diseases and versatility in industrial applications. In particular, microbial transglutaminases (MTG) from Streptomyces bacteria have managed in recent years to evolve from simple food additives to specialized enzymes for the sitedirected modification of therapeutic proteins. The review summarizes relevant studies from the beginning dealing with the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…The series of experiments described above reveal that protein–protein conjugation by MTG can be accelerated under crowded conditions. Although the biological role of MTG in the host organism is unclear, 9 the obtained results imply that the action of TGase with regard to macromolecular substrates may be intrinsically enhanced in a crowded environment, facilitating the formation of biologically important crosslinked products in nature. 37…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The series of experiments described above reveal that protein–protein conjugation by MTG can be accelerated under crowded conditions. Although the biological role of MTG in the host organism is unclear, 9 the obtained results imply that the action of TGase with regard to macromolecular substrates may be intrinsically enhanced in a crowded environment, facilitating the formation of biologically important crosslinked products in nature. 37…”
Section: Resultsmentioning
confidence: 93%
“…8 Therefore, three factors affect enzyme activity under crowded conditions: the size of the crowding reagent, the volume excluded by the crowding reagent, and the size of the enzyme. Because enzymes have a wide substrate scope, 9 the molecular weight of a substrate should also affect the catalytic efficiency of the enzyme under crowded conditions. However, the effect of substrate size on an enzymatic reaction remains unclear because it is difficult to prepare a set of specific substrates with various molecular weights for an enzyme of interest.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirmed that NH 4 + increased the TAP activity at the early stage of fermentation. TAMP (purified from surface colonies on plates) was considered to be involved in TGase activation and regulated by SSTI in S. mobaraensis ( Zotzel et al, 2003a ; Juettner et al, 2018 ; Fuchsbauer, 2021 ). However, the transcript levels of TAMP and SSTI at 24 h were not changed in the presence and absence of NH 4 + (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…When treated at room temperature for 40 h, the TGase activity of the culture supernatant from the 48-h culture broth with NH 4 + addition retained 82% of initial activity, while that from 84-h culture broth without NH 4 + only obtained 65% residual activity ( Figure 3D ). This is probably due to the fact that a lot of proteases were produced at the later stage of S. mobaraensis , resulting in proteolytic degradation of TGase ( Fuchsbauer, 2021 ). Therefore, the reduced fermentation period could not only increase the economy of the TGase but also its storage stability.…”
Section: Resultsmentioning
confidence: 99%
“…Although mTG is widely used in biotechnology, the mechanism explaining its reactivity toward specific glutamine residues relative to others is not well understood. 14 Of particular interest, despite IgG1 human crystallizable fragment (hFc) antibody displaying 8 surface-exposed glutamines, 15 none shows reactivity towards mTG in the context of the native, glycosylated antibody ( Fig. 1A ).…”
Section: Introductionmentioning
confidence: 99%